Educational testing and measurement classroom application and practice - Kubiszyn, Tom; Borich, Gary D. (Hoboken, N.J. Wiley, 2010)
Introduces students to the dramatic developments that have occurred in the field over the last few years. Details the US national policy changes that have fostered the ongoing, dramatic and controversial changes in general education and special education testing and assessment practices.
Chapter 1. An introduction to contemporary educational testing and measurement -- Chapter 2. High-stakes testing -- Chapter 3. Response-to-intervention (RTI) and the regular classroom teacher -- Chapter 4. The purpose of testing -- Chapter 5. Norm- and criterion-referenced tests and content validity evidence -- Chapter 6. Measuring learning outcomes -- Chapter 7. Writing objective test items -- Chapter 8. Writing essay test items -- Chapter 9. Performance-based assessment -- Chapter 10. Portfolio assessment -- Chapter 11. Administering, analyzing, and improving the test or assessment -- Chapter 12. Marks and marking systems -- Chapter 13. Summarizing data and measures of central tendency -- Chapter 14. Variability, the normal distribution, and converted scores -- Chapter 15. Correlation -- Chapter 16. Validity evidence -- Chapter 17. Reliability -- Chapter 18. Accuracy and error -- Chapter 19. Standardized tests -- Chapter 20. Types of standardized tests -- Chapter 21. In the classroom : a summary dialogue -- Appendix A. Math skills review -- Appendix B. Preparing for the Praxis II : principles of learning and teaching assessment -- Appendix C. Determining the median when there are multiple tied scores -- Appendix D. Pearson Product-Moment Correlation -- Appendix E. Statistics and measurement texts -- Appendix F. Answers for practice questions.
Keywords: Educational tests and measurements -- United States